The Roles and Functions of Occupational Health Nurses in Brazil and in the United States Los papeles y funciones del enfermero de salud laboral en Brasil y en los Estados Unidos de America Atribuições e funções dos enfermeiros do trabalho no Brasil e nos Estados Unidos - Maria Helena Palucci Marziale; Oi Saeng Hong; Judy A. Morris; Fernanda Ludmilla Rossi Rocha (Revista Latino-Americana de Enfermagem, 2010)
Cross-sectional exploratory research developed to outline the roles and functions of occupational health nurses (OHNs) in Brazil and compare them with those in the United States. The sample consisted of 154 Brazilian occupational health nurses. First, the instrument Job Analysis Survey of Occupational Health Nursing Practice was translated into Portuguese, followed by data collection and data analysis, comparing the results of the proposed study in Brazil with the findings of a job delineation study conducted in the United States. It was found that most were women, white, between 41 and 50 years of age and working primarily at hospitals or medical centers as clinicians and managers/administrators. Besides, it was found that most Brazilian OHNs spend more time in managerial roles, followed by consultant and educator responsibilities while, in the United States, OHNs spend significantly more time in education/advisory roles. Investigación transversal realizada con el objetivo de definir los papeles y funciones de los enfermeros de salud laboral (ESLs) en Brasil y compararles con los de los Estados Unidos de América (EUA). La muestra fue compuesta por ciento cincuenta y cuatro enfermeros de salud laboral brasileños. Primero, fue realizada la traducción de lo instrumento Job Analysis Survey of Occupational Health Nursing Practice para el Portugués, seguido de la recolecta y análisis de los datos, comparándolos con los hallazgos de un estudio conducido en los EUA. Se encontró que la mayoría eran mujeres, blancas, entre 41 y 50 años e trabajan en hospitales y centros médicos como enfermeros clínicos y administradores. También se encontró que ESLs brasileños dedican más tiempo en funciones administrativas, seguidas de responsabilidades de consultoría y educador, mientras en los EUA los ESLs dedican significativamente más tiempo en funciones educativas y de asesoría. Estudo transversal desenvolvido com o objetivo de delinear as responsabilidades e funções das enfermeiras do trabalho no Brasil e compará-las às atribuições das enfermeiras de saúde ocupacional nos Estados Unidos. A amostra foi composta por 154 enfermeiras do trabalho. Inicialmente, foi realizada a tradução para a língua portuguesa do instrumento de coleta de dados Job Analysis Survey of Occupational Health Nursing Practice, seguido da coleta e análise dos resultados, comparando-os aos dados obtidos num estudo realizado nos EUA. Foi constatado que a maioria das enfermeiras eram mulheres, brancas, com faixa etária entre 41 e 50 anos e trabalhavam em hospitais e centros médicos como enfermeiras clínicas ou administradoras. Além disso, observou-se que as enfermeiras brasileiras despendem maior tempo em funções administrativas, atividades de consultoria e ações educativas, enquanto que as enfermeiras norte-americanas gastam um tempo significativamente maior desenvolvendo papéis educativos e de consultoria.